Educational Dimensions of School Lunch Critical Perspectives (Springer International Publishing, 2018)
School lunch is often regarded as a necessary but inconvenient distraction from the real work of education. Lunch, in this view, is about providing students the nourishment they need in order to attend to academic content and the tests that assess whether content has been learned. In contrast, the central purpose of this collection is to examine school lunch as an educational phenomenon in its own right. Contributing authors-drawing from a variety of disciplinary traditions, including philosophy, sociology, and anthropology-examine school lunch policies and practices, social and cultural aspects of food and eating, and the relation among school food, the environment, and human and non-human animal well-being. The volume also addresses how school lunch might be more widely conceptualized and practiced as an educational undertaking. .